An Integrative Analysis of PIK3CA Mutation, PTEN, and INPP4B Expression in Terms of Trastuzumab Efficacy in HER2-Positive Breast Cancer - Sueta, Aiko (PLoS One, 2014)
The phosphoinositide-3-kinase (PI3K) pathway is commonly deregulated in breast cancer through several mechanisms, including PIK3CA mutation and loss of phosphatase and tensin homolog (PTEN) and inositol polyphosphate 4-phosphatase-II (INPP4B). We aimed to evaluate the predictive relevance of these biomarkers to trastuzumab efficacy in HER2-positive disease. We evaluated the effect of trastuzumab in 43 breast cancer patients with HER2-overexpression who received neoadjuvant treatment. PIK3CA mutation was examined by direct sequencing and digital PCR assay, and PIK3CA copy number was assessed by digital PCR assay of pretreatment tissues. PTEN, pAkt, and INPP4B were assessed by immunohistochemistry. Direct sequencing detected mutant DNA in 21% of all patients, but the incidence increased to 49% using digital PCR. The pathological complete response (pCR) rate in patients with PIK3CA mutations was 29% compared with 67% for those without PIK3CA mutations (P = 0.093), when the mutation was defined as positive if the mutant proportion was more than 10% of total genetic content by digital PCR. Low PTEN expression was associated with less pCR compared to high expression (33% versus 72%, P = 0.034). There were no significant associations of PIK3CA copy number, pAKt, or INPP4B with trastuzumab efficacy. In multivariate analysis, activation of the PI3K pathway due to either PIK3CA mutation or low PTEN were related to poorer response to trastuzumab (OR of predictive pCR was 0.11, 95%CI; 0.03–0.48). In conclusion, activating the PI3K pathway is associated with low pCR to trastuzumab-based treatment in HER2-positive breast cancer. Combined analysis of PIK3CA mutation and PTEN expression may serve as critical indicators to identify patients unlikely to respond to trastuzumab.